2012
DOI: 10.1186/2191-219x-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Microdosimetric analysis of 211At in thyroid models for man, rat and mouse

Abstract: BackgroundThe alpha particle emitter 211At is proposed for therapy of metastatic tumour disease. 211At is accumulated in the thyroid gland in a similar way as iodine. Dosimetric models of 211At in the thyroid are needed for radiation protection assessments for 1) patients receiving 211At-labelled pharmaceuticals where 211At may be released in vivo and 2) personnel working with 211At. Before clinical trials, preclinical studies are usually made in mice and rats. The aims of this study were to develop thyroid mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…However, these results are from animal models and a translation of this data to the human system must be performed with caution, for all three radionuclides, as the photon contribution may be higher in clinical situations. 22,23 Results from the absorbed dose calculations showed that the thyroid received the maximum mean absorbed dose per unit injected activity, for all three radionuclides (Tables 4 and 5). This was expected due to the high activity concentration (400%IA/g for 125 I -, 430%IA/g for 131 Iand 75%IA/g for 211 At).…”
Section: Discussionmentioning
confidence: 97%
“…However, these results are from animal models and a translation of this data to the human system must be performed with caution, for all three radionuclides, as the photon contribution may be higher in clinical situations. 22,23 Results from the absorbed dose calculations showed that the thyroid received the maximum mean absorbed dose per unit injected activity, for all three radionuclides (Tables 4 and 5). This was expected due to the high activity concentration (400%IA/g for 125 I -, 430%IA/g for 131 Iand 75%IA/g for 211 At).…”
Section: Discussionmentioning
confidence: 97%
“…The degree of homogeneity in cellular irradiation - i.e., the fraction of non-hit, single-hit, or multi-hit cells in a population - most likely influences the biological response of a given tissue. This response depends not only on the amount of administered activity and tissue-specific uptake and clearing rates but also on, e.g., organ morphology, tissue structure, and size and density of cells ([ 29 ], Josefsson A, Forssell-Aronsson E. Microdosimetric analysis of the radio halogens 123 I, 124 I, 125 I, 131 I and 211 At, Submitted). Non-homogeneous irradiation may result in non-linear response to absorbed dose on the tissue level and/or increased intensity of, e.g., non-targeted effects [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Percentage of scored vs. filtered transcripts is described as very low , 3%, low 3%-9%, medium 10%-29%, high 30%-49%, and very high $ 50% and highlighted as very light blue, light blue, blue, dark blue, very dark blue, respectively. a mean absorbed dose of 1.2 Gy would correspond to a statistical mean value of 1 a-particle track per thyroid cell (28). Accordingly, absorbed doses of 50 and 500 mGy at 0.064 and 0.64 kBq of 211 At, respectively, would result in around 4% and 40% of single-hit cells in thyroid tissue (17).…”
Section: Discussionmentioning
confidence: 99%